Have IFRS Positive Impact on the Regulatory Accounting Systems in Continental European Countries? - Marcela Žárová; Ladislav Mejzlík (European Financial and Accounting Journal, 2009)
This article investigates statement that IFRS have positive impact on the regulatory system in continental European countries. The accounting regulatory system is used for the purpose of investigation. Authors of the paper developed theoretical scenarios of potential development of the accounting system in the Czech Republic. Rigid architecture of the accounting system, rigid set of accounting rules with no tradition of accounting profession, were considered in the development of potential accounting systems in the Czech Republic. Steps of IFRS implementation are monitored and partial implementation of IFRS into Czech accounting standards are under the criticism of the authors. There is a definite endeavour of the Ministry of Finance to implement some of the best practise of accounting professionals, worldwide respected, into the Czech accounting standards. This endeavour brings sometime very complicated situations and causes breakdown of the accounting system. The paper emphasizes on the most urgent issues. The study provides clear evidence under which conditions, in the system with continental European law, could the national accounting standards be developed through a formal system of due process. It can therefore be assumed that the impact of IFRS on accounting regulatory system in other continental European countries is similar.
Keywords: M41; 650; Regulatory systems; IFRS; Due process